Empowerment of Nutrition Educators for Strengthening Obesity Prevention in Elementary School Students in Parepare - Andi Imam Arundhana Thahir; Rahayu Indriasari; Henrick Sampeangin; Thahir Haning; Khadijah Nur Hasanah Assegaf; Muhammad Rachmat (Universitas Muhammadiyah Surakarta, 2026)
The double burden of nutritional problems among schoolchildren in Indonesia—relected by soaring rates of stunting and obesity—poses new challenges to efforts aimed at improving community nutrition. In Parepare City, South Sulawesi, a clear nutrition transition is observed, with rising cases of obesity in the school environment. This community service activity was designed and implemented a school‐based empowerment program called “Sahabat Gizi” (Nutrition Friends) peer educators, aiming to strengthen obesity prevention through balanced nutrition education, environmental adjustments, and reinforcement of school policies. The program was carried out in three phases: preparation, training, and evaluation, involving teacher mentors and students who acted as agents of change. Pre‐ and post‐test results indicated signiicant improvements in participant knowledge and communication skills, while their attitudes remained relatively stable. The training effectively increased participants’ knowledge (87.5%) and communication skills (43.8%), while over 90% showed stable attitudes with no signiicant changes. Independent initiatives undertaken by peer educators reinforced understanding and honed nutrition communication skills effectively while fostering positive healthy behavior norms. Program indings suggest that the peer educator model applied in schools successfully increased students’ knowledge of balanced nutrition and contributed to obesity prevention. However, to ensure sustainability and strengthen positive attitudes, more intensive policy support is needed.